Aids : A Rampant Intruder - Chandra, Suresh (Indian Journal of Community Health, 2004)
The HIV/AIDS epidemic represents the most serious public health problem in India. There is no denial of the enormity of the problem. The prevalence of infection in all parts of the world highlights the spread from urban to rural areas and from high risk to general population. It is estimated that as on end of year 2004, 39.4 million people were infected with the virus. Migration of labour, low literacy levels leading to low awareness, gender disparities, prevalence of sexually transmitted diseases and reproductive tract infections are some of the factors attributed to the spread of HIV/AIDS. 4.9 million ( 4.3 million - 6.4 million) people have aquired HIV infection only in one year of span - 2004. The global AIDS epidemic killed 3.1 million ( 2,8 million- 3.5 million) people in the past year.